The effect of aclarubicin (acl) on human erythrocytes - Witczak, Piotr; Marczak, Agnieszka (Current Topics in Biophysics, 2012)
The present study examines the influence of aclarubicin (ACL) on human red blood cells with a focus on the generation of reactive oxygen species (ROS). A statistically significant increase in ROS levels was observed for all the tested concentrations of aclarubicin (1-20 nM). The depletion of catalase activity and elevated metHb content were also observed. On the other hand, changes in reduced glutathione (GSH) and total glutathione concentrations were not statistically significant. The presented results confirm important role of ROS in ACL cytotoxic activity.